2019
DOI: 10.1038/s41433-019-0679-5
|View full text |Cite
|
Sign up to set email alerts
|

How do different lighting conditions affect the vision and quality of life of people with glaucoma? A systematic review

Abstract: from eligible studies regarding study design, participant characteristics, outcomes and results. Quality of included studies was critically appraised. Of 8437 studies, 56 eligible studies were included. Studies investigated the effects of lighting on the following themes among people with POAG: QoL (18/56), psychophysical measures (16/56), functional vision (10/56), activities of daily living (10/56) and qualitative findings (2/56). POAG negatively affects low-luminance contrast sensitivity, glare symptoms, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…To date, adaptation to light levels has been limited to a few performance-based mobility 41 43 and driving studies 41 46 investigating glare disability, in spite of it being such a frequently reported problem for patients with vision impairment. 3 , 5 , 16 , 17 , 47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, adaptation to light levels has been limited to a few performance-based mobility 41 43 and driving studies 41 46 investigating glare disability, in spite of it being such a frequently reported problem for patients with vision impairment. 3 , 5 , 16 , 17 , 47 …”
Section: Discussionmentioning
confidence: 99%
“… 1 4 Even in the early stages of eye disease, adults with vision impairment report difficulties with night driving, walking at night, seeing steps, reading under dim illumination, glare, and adapting to changes in illumination. 1 , 3 , 5 , 6 The consequences can be serious, including motor vehicle collisions, particularly involving pedestrians and cyclists, 7 , 8 falls, 9 12 and emotional distress. 5 , 13 Measuring these effects has become increasingly important to better understand the problems experienced by adults with vision impairment under low luminance, to design interventions to prevent physical and psychological injury and to develop measures for evaluating and monitoring changes in performance following eye therapies and vision interventions.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal simulator would also take into account the fact that, for many patients, the extent/quality of their vision loss varies, depend on their own physiological state or their current viewing conditions (e.g., level of ambient illumination). Thus, it has been observed that some glaucoma patients exhibit a greater loss of vision under home-lighting, than when assessed in a well-lit eye clinic 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, instead of reporting these symptoms, the patients complain of blurred vision and increased requirement of light for work. 13 Lack of awareness about the disease and poor socioeconomic conditions of the patients contribute to late presentation. This may be the possible reason that treatable and reversible causes of decreased vision in glaucoma patients remain undiagnosed, untreated and overlooked.…”
Section: Discussionmentioning
confidence: 99%